A grammar of institutions for complex legal topics: Resolving statutory multiplicity and scaling up to jurisdiction‐level legal institutions. - DeMattee, Anthony J. (Policy Studies Journal, 2023)
Laws are a unique type of primary data: they structure our everyday interactions and are publicly available to all people. How can we assess the law's effect when multiple overlapping and cross‐referencing statutes constrain and incentivize behavior simultaneously? I present a principled method for aggregating the legal rules coded in multiple laws into a single legal institution to help us understand and better characterize complex, interconnected, and sometimes contradictory bundles of legal rules. The method utilizes Institutional Grammar (IG), which scholars have used to code legal language into comparable institutional statements. The method is amenable to any legal topic and is especially appropriate when multiple statutes simultaneously comprise the legal institution in a single jurisdiction. To illustrate, I draw on the laws regulating civil society organizations (CS0s), which offer a valuable and substantively important prism to study legal texts as the cause of social phenomena or the outcome of a political process. I discuss my proposed method in three parts: first, why using IG enhances a coding instrument's validity; second, how an IG‐based instrument allows researchers to scale up coded values of separate laws into a jurisdiction‐level value; finally, I compare techniques for estimating descriptive measures of a jurisdiction's legal institution.